Dampak Pemberitaan Penyalahgunaan Formalin Terhadap Kinerja Industri Tahu Di Daerah Istimewa Yogyakarta - Triwara Buddhisatyarini (Agricultural Socio-Economics Journal, 2012)
This research aims to knows production, net revenue and profit changes, and what were the producers effort to return consumers believing to product of tofu home industry. The respondence at the research were 37 producers of tofu home industry in Daerah Istimewa Yogyakarta which registered in Trade and Industrial Departement. Data used were one month before issues (December 2005) and data of one month after issues (January 2006). Quantitative analysis carried out include: cost analysis, revenue analysis, analysis of revenue and profit before and after the outbreak of formaldehyde issues. While the descriptive analysis includes profiles of entrepreneurs know and efforts made to tackle the issue of formalin entrepreneurs. The result of production analysis were,  production of Sleman tofu home industry was down 30% rarely,production of Bantul was down 42% rarely and production of Yogyakarta was down 63% rarely. The result or revenue analysis were, 57% net revenues of Sleman tofu home industry was down rarely, 31% of Bantul tofu home industry and 61% of Yogyakarta. The result of profit analysis were, 31% profit of Sleman tofu home industry was down rarely, 30% of Bantul and 61% of Yogyakarta, which highest value of down rate effect to Yogyakarta city tofu home industry. To counter formalin issues, producers haven’t intensive effort, there was interpersonal communication only at limited environment. Key words :  formalin abuse, production, profit, issues counter